Relationship of pre-hospital clinical status with behavior of intracranial pressure and outcomes in pediatric patients with severe head trauma. - Abreu Pérez, Daysi; Lacerda Gallardo, Angel Jesus; Galvez., Jose Antonio (Medicina Clínica y Social, 2023)
Introduction: The prehospital phase of the management of pediatric severe traumatic brain injury may have a direct influence on the results. Objective: To evaluate the influence of prehospital variables on intracranial pressure and the results in pediatric patients with severe TBI. Method: A descriptive study of 41 pediatric patients who were admitted to the medical emergency department and later admitted to the pediatric intensive care unit due to severe head trauma was carried out between January 2003 and December 2018. Results: children aged 5-17 years predominate, and the highest number of cases were received between 0-3h at the neurotrauma center. Of the 41 cases, 27 arrived with a non-expedited airway and hypoxia was verified upon arrival by pulse oximetry. A correlation was observed between arterial hypotension on admission and elevated intracranial pressure in 9 of 15 children (60%) and in the deceased (40%). Discussion: Clinical conditions, oxygenation, arterial hypotension, and treatment in the prehospital phase may influence the state of intracranial pressure and other intracranial variables in pediatric patients with severe head injury.